Repetitive Elements, Sequence Turnover and Cyto-Nuclear Gene Transfer in Gymnosperm Mitogenomes - Liu, Hui; Zhao, Wei; Zhang, Ren-Gang; Mao, Jian-Feng; Wang, Xiao-Ru (Frontiers in Genetics, 2022)
Among the three genomes in plant cells, the mitochondrial genome (mitogenome) is the least studied due to complex recombination and intergenomic transfer. In gymnosperms only ~20 mitogenomes have been released thus far, which hinders a systematic investigation into the tempo and mode of mitochondrial DNA evolution in seed plants. Here, we report the complete mitogenome sequence of Platycladus orientalis (Cupressaceae). This mitogenome is assembled as two circular-mapping chromosomes with a size of ~2.6 Mb and which contains 32 protein-coding genes, 3 rRNA and 7 tRNA genes, and 1,068 RNA editing sites. Repetitive sequences, including dispersed repeats, transposable elements (TEs), and tandem repeats, made up 23% of the genome. Comparative analyses with 17 other mitogenomes representing the five gymnosperm lineages revealed a 30-fold difference in genome size, 80-fold in repetitive content, and 230-fold in substitution rate. We found dispersed repeats are highly associated with mitogenome expansion (r = 0.99), and most of them were accumulated during recent duplication events. Syntenic blocks and shared sequences between mitogenomes decay rapidly with divergence time (r = 0.53), with the exceptions of Ginkgo and Cycads which retained conserved genome structure over long evolutionary time. Our phylogenetic analysis supports a sister group relationship of Cupressophytes and Gnetophytes; both groups are unique in that they lost 8–12 protein-coding genes, of which 4–7 intact genes are likely transferred to nucleus. These two clades also show accelerated and highly variable substitution rates relative to other gymnosperms. Our study highlights the dynamic and enigmatic evolution of gymnosperm mitogenomes.